Caribbean regional integration process : an assessment - Lewis, David E. (SELA CaracasVE, 1996)
Analyses the integrationist and economic cooperation experience in the Caribbean Basin from an institutional perspective. Looks at the intra-regional experience as well as the initiatives for extra-regional cooperation. Focuses on the establishment of the Association of Caribbean States and on the prospect for the regional integration process in the Caribbean.